Caries y otras condiciones de la boca de niñas escolares de diferente nivel económico y social - Pauly S., Raymond (1956)
1. So as to obtain solid bases for an effective dental education of costarican children, the Department of Infantile and Preventive Odontology of the Faculty of Odontology of the University of Costa Rica has begun a statistical study of caries and other oral conditions among school children of San José. 2. This paper represents the first part of the study, the female cases. It deals on a comparative analysis between two groups of school girls of different economic and social level, designated as Group A and Group B, and com prising a total of 349 samples. 3. The investigation was carried out by means of questionings and clinical examinations, and contemplated the following points: I. General conditions: A. Oral conditions. B. Sugar consumption. C. Frequency of dental examinations. D. Oral hygiene. II. Condition of the teeth. A. Permanent dentition. a. DMF for each tooth and surface. b. Number of caries. c. Number of obturations. d. Dental health index. e. Dental mortality index. f. Relation among occlusated, proximal, and other types of canes. g. Index of affection of the first molar. B. Deciduos dentition: a. dmf for each tooth and surface. b. Number of caries. c. Number of obturations. d. Relation among occlusal, proximal, and other types of caries. e. Dental mortality. 4. The results are presented in seven tables and ten graphs, and show a manifest superiority of conditions in every respect among the girls of Group B.